EFFECT OF SEED PRIMING WITH BOTANICAL LEAF EXTRACTS ON SEED QUALITY AND YIELD OF MAIZE HYBRID, COH(M) 4 - S. SRIMATHI, J. GOKULAKRISHNAN and M. PRAKASH* (The Journal of Research ANGRAU, 2021)
The investigation was carried out to study the effect of seed priming with botanical leaf extractson seed quality and yield of maize hybrid, COH(M) 4. The seeds of maize hybrid, COH(M) 4 wereprimed with various leaf extracts at 10% concentration viz., Papaya (Carica papaya), Pungam(Pongamia pinnata), Prosopis (Prosopis juliflora), Adathoda (Justicia adhatoda), Tulsi (Ocimumtenuiflorum), Neem (Azadirachta indica) and Moringa (Moringa oleifera) along with a control. Thestudy revealed that the seeds primed with 10% prosopis leaf extract followed by 10% moringa leafextract recorded higher seed quality characters like germination percentage, speed of germination,seedling length, dry matter production, vigour index I and II. In the field evaluation, seeds primed with10% prosopis leaf extract followed by 10% moringa leaf extract recorded higher seed yield and yieldattributing parameters like cob length and girth, total number of seeds cob-1, 100 grain weight, grainyield per ha and harvest index.